2002
DOI: 10.1161/01.cir.0000032889.55215.f1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Myoblast Transplantation on Regional Structure and Function After Myocardial Infarction

Abstract: Background Transplantation (Tx) of skeletal myoblasts (SM) within an infarcted myocardium improves global left ventricular (LV) function, although a direct systolic effect remains controversial. Methods and Results Global and regional LV functions were studied in a sheep model (n=16) of infarction before (baseline), and 4 (M4), and 12 (M12) months after in-scar injections of autologous SM or culture medium (CM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Because of the expectation of these self-healing conductive hydrogels to be used in the cell delivery for cardiac repair, the cell delivery ability of this hydrogel was further investigated. H9c2 cells had been widely used in the regeneration of cardiac tissues. , Skeletal myoblasts had been demonstrated to have the ability to differentiate into myotubes or myocardium which was promising in improving cardiac function postinfarction. ,, Thus, C2C12 myoblasts and H9c2 cardiac myoblasts were chosen to measure the cell delivery ability of the hydrogels. It was tested for 7 days and the delivered cell numbers were monitored every day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the expectation of these self-healing conductive hydrogels to be used in the cell delivery for cardiac repair, the cell delivery ability of this hydrogel was further investigated. H9c2 cells had been widely used in the regeneration of cardiac tissues. , Skeletal myoblasts had been demonstrated to have the ability to differentiate into myotubes or myocardium which was promising in improving cardiac function postinfarction. ,, Thus, C2C12 myoblasts and H9c2 cardiac myoblasts were chosen to measure the cell delivery ability of the hydrogels. It was tested for 7 days and the delivered cell numbers were monitored every day.…”
Section: Resultsmentioning
confidence: 99%
“…29,60 Skeletal myoblasts had been demonstrated to have the ability to differentiate into myotubes or myocardium which was promising in improving cardiac function postinfarction. 8,9,61 Thus, C2C12 myoblasts and H9c2 cardiac myoblasts were chosen to measure the cell delivery ability of the hydrogels. It was tested for 7 days and the delivered cell numbers were monitored every day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated both in large and small animal models that these cells engraft, differentiate into skeletal fibers, acquire certain characteristics of cardiac muscle and contribute to improve cardiac function and animal survival. 16,20,21,23 Very recent reports in patients with myocardial infarction have shown that skeletal autologous myoblast can survive after transplantation and form viable grafts in heavily scarred human myocardial tissue thus providing a proof of principle. 17,22,31 Although skeletal myoblast can be successfully transplanted, the percentage of cells that survive and differentiate into functional tissue is currently unknown and some reports suggest that it may be lower than 1%.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of skeletal myoblast in animal models of myocardial infarction and more recently in humans has been associated with successful engraftment of skeletal muscle fibers, graft survival and functional benefit. 7,[14][15][16][17][18][19][20][21][22] Although controversial, some evidences suggest that skeletal muscle progenitors may acquire certain characteristics of cardiac muscle both in vitro and in vivo. 19,[22][23][24] We have examined, in a phase I clinical study, the feasibility and safety of intramyocardial transplantation of autologous skeletal myoblast cultured in vitro with autologous serum in patients with old myocardial infarction undergoing coronary artery bypass surgery.…”
Section: Introductionmentioning
confidence: 99%